Evaluation of post COVID-19 energy poverty and global trading impact on energy affordability - Schislyaeva, Elena Rostislavovna; Saychenko, Olga Anatolievna (Frontiers in Energy Research, 2022)
Energy poverty become a serious global problem after COVID-19 among the developing and developed countries that must have to be addressed to meet United Nations Sustainable Development Goals (SDGs). Moreover, the factors contributes to energy poverty have given little attention. The study aims to overlooked on the energy affordability and accessibility among the Europeans living in Energy poverty. Therefore, study mainly concerning on the effecting factors such as bilateral commerce, globalization, and the quality of bureaucracy that possibly affect energy poverty. The influence of bilateral commerce on energy poverty was investigated using many robust panel data approaches, including cross-sectional autoregressive distributed lag (CS-ARDL), common correlated effects generalized method of moments (CCE-GMM), and instrumental variable regression. Annual data utilizes from European nations (from 2000 to 2019). According to the econometric findings, bilateral commerce enhances energy accessibility while raising energy prices. Economic globalization was meant to raise energy costs and restrict fuel access for Europe’s poorest citizens. Study suggested that bilateral trade should be assessed to ensure energy demand and supply conditions meet to keep the energy pricing in the afforadbale range especially among the low income families in the Europen countries. Across models, these results are consistent, allowing us to propose fresh energy accessibility and affordability conclusions in line with the SDGs.